Lymph node metastasis in early gastric cancer - Bravo Neto,Guilherme Pinto (2014)
OBJECTIVE: to evaluate the incidence of lymph node metastasis in early gastric cancer, identifying risk factors for its development. METHODS: we conducted a prospective study of patients with gastric cancer admitted to the Section of the Esophago-Gastric Surgery of the Surgery of Service HUCFF-UFRJ, from January 2006 to May 2012. RESULTS: the rate of early gastric cancer was 16.3%. The incidence of nodal metastases was 30.8% and occurred more frequently in patients with tumors with involvement of the submucosa (42.9%), in those poorly differentiated (36.4%), in tumors larger than 2 cm (33.3%) and in type III ulcerated lesions (43.8%). CONCLUSION: the incidence of lymph node metastases in patients was very high and suggests that one should keep the radicality of resection in early gastric cancer, particularly in relation to D2 lymphadenectomy, recommended for advanced gastric cancer. Conservative resections, with lymphadenectomies smaller than D2, should be performed only in selected cases, well-studied as for the risk factors of lymph node metastasis. Despite the small number of cases did not permit to relate the rate of lymph node metastasis to the risk factors considered, we noted a strong tendency for the occurrence of these metastases in the poorly differentiated, type III, larger than 2 cm tumors, and in the Lauren diffuse types.